Intermediaries in Strategic Procurement: Opportunities and Obstacles for Public Organizations: A Critical Review - Bhenu Artha; Syakdiah; Oktiva Anggraini; Retno Kusumawiranti; Suwarjo; Sri Lestari Harjanta (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study presents a critical review of research exploring the role of intermediaries in strategic public procurement, a sector transitioning from traditional cost reduction to long-term societal goals such as innovation and sustainability. As public organizations increasingly rely on third-party brokers to manage complex markets, there is an urgent need to evaluate how these hybrid governance models affect strategic capacity and traditional control structures. The primary objective of this review is to systematically analyze the influences of intermediaries on organizational accountability and long-term market dynamics. Using a critical literature review methodology, the research evaluates the methodological rigor, theoretical underpinnings, and empirical findings of existing scholarship, specifically focusing on a 2025 case study of the Swedish consultancy and medical technology sectors. The findings highlight several strengths, including a highly relevant research agenda and a holistic multi-stakeholder approach that incorporates diverse voices from purchasers and suppliers. However, the review identifies significant limitations: a narrow geographical and sectoral scope, potential self-selection bias in sampling, and a surface-level application of contingency theory that lacks analytical depth. Furthermore, the study notes that causal claims regarding intermediaries undermining procurement are not fully supported by the qualitative data. The review concludes that while the research provides valuable insights into implementation challenges and accountability tensions, its generalizability remains restricted, and practitioners require more evidence-based, actionable solutions to balance administrative efficiency with strategic public value.